If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (20x + 4) = (6x + 4) Reorder the terms: (4 + 20x) = (6x + 4) Remove parenthesis around (4 + 20x) 4 + 20x = (6x + 4) Reorder the terms: 4 + 20x = (4 + 6x) Remove parenthesis around (4 + 6x) 4 + 20x = 4 + 6x Add '-4' to each side of the equation. 4 + -4 + 20x = 4 + -4 + 6x Combine like terms: 4 + -4 = 0 0 + 20x = 4 + -4 + 6x 20x = 4 + -4 + 6x Combine like terms: 4 + -4 = 0 20x = 0 + 6x 20x = 6x Solving 20x = 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 20x + -6x = 6x + -6x Combine like terms: 20x + -6x = 14x 14x = 6x + -6x Combine like terms: 6x + -6x = 0 14x = 0 Divide each side by '14'. x = 0 Simplifying x = 0
| 10.410= | | 3x(2-2x)=-6x(x-1) | | 2w-54=-w+21 | | 7a+4=4a | | 2=5y-3 | | H=16t^2+352t | | 15x-9=3x+2 | | (8x+18)=(6x+4) | | F=1/2gq | | 5-3s=-s-5 | | 3n-21=2n | | 8x+18=6x+4 | | 5+4v=29 | | 8x+2-3=1 | | 3x-1=77 | | 0p+9-11-p=2(2p+4)-3(2p-2) | | 2v+5=4u+13 | | 126=-9(4+r) | | 2p+9=3p-6 | | p-12=34+q | | Y-18=x+5 | | 3p=7(9p+2) | | 3(6x+2)=30 | | 4x-2(x-3)=-9+5x-9 | | 13.3+7u=-4.2 | | 7+5p=6p | | 7+5(2x+3)-9= | | 3x+8x-2=108 | | 27=3u-15 | | 10m+8m=108 | | -12.72+(-1.008)-(-4.3)+9.17= | | 7w-11w=8 |